A new specimen setup for high precision uniaxial tension-compression tests of rubber. (2018) - Kanzenbach, Lars; Oelsch, Erik; Stockmann, Martin; Ihlemann, Jörn
Abstract: The aim of this contribution is the development of a new test specimen, which allows the investigation of rubber in combined uniaxial tension-compression tests. In comparison to the standard dumbbell, which also allows combined tests, the homogeneity in the measuring zone is significantly improved. Furthermore, the achievable amount of compression is increased substantially. The test specimen itself has a slender dumbbell shape. By a special design of the mounting geometry, a homogeneous strain field can be achieved. With the developed specimen setup, the phenomenological characteristics of rubber like Payne-effect, Mullins-effect, recovery and relaxation behavior can be investigated in more detail.